(untitled) (European Bison Conservation Newsletter, 2009)
The establishment of European bison breeding centre in the Prioksko-Terrasnyjj reserve was caused by the necessity to preserve one of the most valuable representatives of a wild fauna on the European part of Russia. On the beginning there were many question how to organize reserve to fulfill needs of species preservation. In the first period the priority was to create center for European bison breeding, which assures guard for animals, condition for reproduction and lack of intervention into natural “wild” way of life. The process of captive breeding was needed to reduce the losses of the genetic variability and to develop the European bison population for reintroduction.